3(2x-5)+8x-6=x/2-(5x+3)

Simple and best practice solution for 3(2x-5)+8x-6=x/2-(5x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-5)+8x-6=x/2-(5x+3) equation:


3(2x-5)+8x-6=x/2-(5x+3)

We simplify the equation to the form, which is simple to understand
3(2x-5)+8x-6=x/2-(5x+3)

Reorder the terms in parentheses
+(+6x-15)+8x-6=0.5x-(5x+3)

Remove unnecessary parentheses
+6x-15+8x-6=0.5x-(+5x+3+)

Remove unnecessary parentheses
+6x-15+8x-6=0.5x-5x-3

We move all terms containing x to the left and all other terms to the right.
+6x+8x-0.5x+5x=-3+15+6

We simplify left and right side of the equation.
+18.5x=+18

We divide both sides of the equation by 18.5 to get x.
x=0.97297297297297

See similar equations:

| 7(9+15e)+19-49e+70+10e=88 | | 7(9+15e)+19-49e+70+10e=90 | | 20+17w=6+15w | | 7(9+15e)+19-49e+70+10e=91 | | -0.5+2y=-1 | | 7(9+15e)+19-49e+70+10e=98 | | 3(x+6)=81x | | -540.00+13.5g=4158.00 | | 3r-21=7 | | -540.00+13.5g=1500.00 | | 4x+121=2x+123 | | 6d-10= | | 17(t-3)(t-8)=0 | | 15.4+3.5h=1.2h-6 | | 3.3n+3.4=54+6n | | 12d-84= | | -6+15g=9+15g | | 8y-30=34 | | 3(y+2)=y+24 | | 2x+15=14-x | | (-8x+2y)(-4x+4y)= | | c=(3x+y-4)*5-5y+3 | | 5-15t=-15t-14 | | 4+14x=2x-8+12x | | -18n+6n-3=5-12n | | 965.3616=87.92*r^2+62.17*r | | -6y-1=-9y+2 | | 7x-5+3x=75 | | -6-10v=-10v-6 | | w^2-2w=-67 | | -4m+7=7-4m | | 3(p-3)=24 |

Equations solver categories